Synthesis, Characterization and Cytotoxic Activity of Some Pyrimidine Derivatives - Ahmed, Salman Ali; Naji, Tamara Sami; Mohammad, Farooq Ibrahem (Al-Nahrain Journal of Science, 2013)
Synthesis of some pyrimidine derivatives which plays an important role in the medicinal chemistry because it possesses promising cytotoxic activity. The synthesized compounds were characterized by UV-Visible and FT-IR spectral data. Some of the new compounds were evaluated for their potential cytotoxicity against two different human cancer cell lines HepG2 (hepatocellular carcinoma) and MCF-7 (breast adenocarcinoma) in vitro, using Neutral Red and MTT assays. The synthesized compounds were active against two cell lines under study and a toxic effect was clear with a significant difference at the level of probability (p< 0.0001) and this effect was contrasted among different concentrations for each synthesized compound.